TagaTRIS a content-based Tagalog text readability indexing system using concept indexing with K-means algorithm - Bosque, Michelle Louise S.; Ledesma, Rommel R.; Loberas, Hazel M. (2011.)
In this paper, we present a content-based readability indexing technique using the new dimensionality reduction algorithm called Concept Indexing (CI). Simulations were conducted on Adarna House books and University of the Philippines Integrated School (UPIS) books and essays to compare the algorithm's overall performance to Latent Semantic Indexing (LSI), which has been well-known for its empirical success. Furthermore, the effects of vector space weighting schemes, stemming, stopwords removal, and dimensionality on both algorithms were investigated. Based on the results, CI can reach up to 94% overall accuracy (OA) and can also outperform LSI by almost 4% in the average overall acuracy (OA) across all grade levels.
With user manual (bound with the main text).
Thesis (B.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Latent semantic indexing; Tagalog language; K-means algorithm; Concept indexing; TagaTRIS